2016
DOI: 10.1016/j.bjid.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of Mycobacterium tuberculosis pili (MTP) as an adhesin, invasin, and cytokine inducer of epithelial cells

Abstract: This study was undertaken in order to assess the involvement of Mycobacterium tuberculosis pili (MTP) as an adhesin, invasin, and cytokine inducer in the M. tuberculosis-epithelial cell interaction. A MTP-deficient strain of M. tuberculosis demonstrated a significant reduction of 69.39% (p=0.047) and 56.20% (p=0.033) in its ability to adhere to and invade A549 pulmonary epithelial cells, respectively, in comparison with the wild-type strain. Complementation of the MTP-deficient mutant restored its adhesion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
0
20
0
2
Order By: Relevance
“…AbmR likely mediates the serum‐dependent adherence and/or invasion of non‐phagocytic lung epithelial cells through factors other than the adhesin HBHA, as we did not observe changes in HBHA expression that could account for this phenotype. Multiple additional proteins have been shown to mediate the attachment of Mtb to lung epithelial cells, some of which are unique to TB complex mycobacteria (Mueller‐Ortiz et al ., ; Reddy and Hayworth, ; Vidal Pessolani et al ., ; Ramsugit et al ., ). While we did not observe dysregulation of these factors at the mRNA level (data not shown), the abundance of these proteins may be altered at the translational level by ncRNAs (such as Mcr11) regulated by AbmR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AbmR likely mediates the serum‐dependent adherence and/or invasion of non‐phagocytic lung epithelial cells through factors other than the adhesin HBHA, as we did not observe changes in HBHA expression that could account for this phenotype. Multiple additional proteins have been shown to mediate the attachment of Mtb to lung epithelial cells, some of which are unique to TB complex mycobacteria (Mueller‐Ortiz et al ., ; Reddy and Hayworth, ; Vidal Pessolani et al ., ; Ramsugit et al ., ). While we did not observe dysregulation of these factors at the mRNA level (data not shown), the abundance of these proteins may be altered at the translational level by ncRNAs (such as Mcr11) regulated by AbmR.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of serum strongly influences these interactions (Bermudez and Sangari, 2001). Several bacterial factors involved in Mtb's adherence and invasion of host cells have been described, but gene deletion studies suggest additional undiscovered bacterial components may be involved in this initial step of pathogenesis (Menozzi et al, 1996;Pethe et al, 2001;Mueller-Ortiz et al, 2002;Reddy and Hayworth, 2002;Vidal Pessolani et al, 2003;Menozzi et al, 2006;Ramsugit et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pili are recognized by IgG antibodies contained in sera of patients with active tuberculosis, indicating that the bacilli produce pili or pili‐associated antigen during human infection . M. tuberculosis produces two pili types: curli and type IV pili . Purified M. tuberculosis pili are composed of low molecular‐weight protein subunits, designated as Rv3312A .…”
Section: Roles and Structural Features Of Mycobacterial Adhesinsmentioning
confidence: 99%
“…Numerous M. tuberculosis proteins have been documented to function in the attachment to host components, including pili and curli . Also, dissemination from the site of primary infection involves interactions of M. tuberculosis with epithelial cells through a surface protein called heparin‐binding haemagglutinin, HBHA .…”
Section: Introductionmentioning
confidence: 99%
“…In analyzing the process of attachment, it was found that a variety of adhesins were necessary for the infection of M. tuberculosis with the lung. Pili are a surface structure similar to hair, and their distal tip contains an adhesin, Curli Pili encoded by Rv3312A , which binds to laminin on macrophages and epithelial cells surface (7, 8). However, M. tuberculosis has also been found to contain a large of adhesins that do not involve pili.…”
mentioning
confidence: 99%